The differentiation of extrahepatic biliary atresia from the neonatal hepatitis syndrome - Daubenton, John David (Division of Nuclear Medicine, 2017)
The differentiation, in an infant with cholestasis, between extrahepatic biliary atresia (EHBA) and the neonatal hepatitis syndrome (NHS) is important in that laparotomy is always indicated in EHBA but is undesirable in NHS. This differentiation is particularly difficult in those infants with complete cholestasis. Hepatobiliary scintigraphy is a commonly used investigation in infants with obstructive jaundice. The scintigraphic demonstration of excretion into the gut excludes extrahepatic obstruction, however, absence of excretion may be due to EHBA, severe cholestasis with patent extrahepatic bile ducts or poor uptake of the agent, and is therefore not diagnostic. This study has examined the quantitative measurement of the hepatic uptake of p-butyl IDA and Sn colloid, and an estimation of liver shape, in a group of patients with complete cholestasis in whom conventional scan interpretation, based on excretion into the-gut, would not be useful. The scans were recorded as dynamic studies and the resultant time-activity curves were subjected to curve fitting to calculate a rate constant for uptake of radiopharmaceutical. Liver shape was determined from the anterior static image of the colloid scan. The results show a significant difference between the EHBA and the NHS patients in the rate of uptake of p-butyl IDA, in the ratio of the rate of uptake of p-butyl IDA/the rate of uptake of colloid and in the measurements used to express liver shape. Using this method of scan interpretation, a diagnostic accuracy of 85% was achieved in this study of patients who clinically, and on scan, had no evidence of bile flow. Hepatic scintigraphy is therefore a useful investigation in the diagnostic work-up of infants presenting with obstructive jaundice even when bile flow is completely absent.